Acesso de lésbicas, gays, bissexuais e travestis/transexuais às Unidades Básicas de Saúde da Família - Oliveira, Geane Silva (2018)
Objective: to understand the access of lesbians, gays, bisexuals and transvestites/transsexuals to the Basic Family Health Units. Methods: qualitative research held with 54 patients. A semi-structured interview and the free association test were used. The data were processed by the software IRaMuTeQ® and submitted to the technique of Content Analysis in the thematic modality. Results: six categories emerged: Silencing regarding sexual orientation and gender identity – access is facilitated as they do not reveal themselves; Invisibility and indifference to legal political references - antagonism between the paradigm thought and executed; Homophobic manifestations and effects on access - restricted use of the service; Embarrassment and distancing - removal and search for private services; Des (humanized) and unethical practices - lack of awareness, secrecy; and Stigma and access - permanence of stigmata between Acquired Immunodeficiency Syndrome and homosexuality. Conclusion: the access to health services is limited with intolerance, constraints, exclusionary and aerial positions.